Observation on the clinical efficacy of transparent cap-assisted endoscopic injection of lauromacrogol sclerosing agent in the treatment of internal hemorrhoids of grade Ⅱ-Ⅲ - Wang Zhenkai; Liu Xiang; Chen Wanzhen; Yang Xiaoqian; Liu Dan (结直肠肛门外科)
[Objectives] To observe the efficacy of transparent cap-assisted endoscopic injection of lauromacrogol sclerosing agent in the treatment of internal hemorrhoids of grade Ⅱ-Ⅲ. [Methods] A retrospective analysis of clinical data of 244 patients with internal hemorrhoids of grade Ⅱ-Ⅲ admitted to the endoscopy center of Nanjing Hospital of Traditional Chinese Medicine from January 2019 to January 2022. Patients were divided into an observation group (n＝122, treated with transparent cap-assisted endoscopic injection of lauromacrogol sclerosing agent) and a control group (n＝122, treated with PPH). Operation time, hospitalization time, postoperative complications, postoperative recurrence, clinical efficacy, and satisfaction of the two groups were recorded and compared. [Results] The operation time and hospitalization time in the observation group were shorter than those in the control group (P<0.05). The total incidence of complications such as anal edema, fever, bloody stool, urinary retention, and anal stenosis within 24 hours after operation in the observation group was lower than that in the control group (2.5% vs.41.8%, P<0.001), and satisfaction was higher than that in the control group (96.7% vs.77.0%, P<0.001); There was no significant difference in the recurrence rate (8.2% in the observation group vs.4.9% in the control group) and the total effective rate (96.7% in the observation group vs.98.4% in the control group) between the two groups (P>0.05). [Conclusion] Transparent cap-assisted endoscopic injection of lauromacrogol sclerosing agent for the treatment of internal hemorrhoids of grade Ⅱ-Ⅲ has the characteristics of simple operation, rapid recovery, safety, efficacy, and repeatability, making it worthy of clinical application.